Effects of interferential stimulation on clinical symptom and urodynamic findings in women with voiding dysfunction: A protocol of randomized clinical trial - Seyedeh Saeideh Babazadeh-Zavieh; Fahimeh Karshenas; Sona Tayebi; Niloofar Rabiei; Seyed Mohammad Jafar Haeri (PLoS ONE, 2025)
Background Voiding dysfunction, characterized by abnormally slow and/or incomplete micturition, is a clinical challenge that significantly impacts quality of life among women. Dysfunctional voiding, a subtype of voiding dysfunction is identified by intermittent and/or fluctuating urine flow caused by involuntary periurethral striated muscle contractions during voiding in individuals without neurological abnormalities. Interferential stimulation is a non-invasive surface electrical stimulation modality widely employed in physiotherapy. The current evidence supports its clinical efficacy in managing both urinary and fecal disorders. However, its role in treating dysfunctional voiding in women remains understudied. Thus, we present a study protocol to investigate the effects of interferential electrical stimulation on clinical symptoms and urodynamic findings in women with dysfunctional voiding. Methods This double-blind, randomized controlled trial will employ a parallel-group design and will be conducted at the Physiotherapy Clinic of Iran University of Rehabilitation Sciences, Tehran, Iran. The study population will comprise women aged 18–50 years diagnosed with dysfunctional voiding. This trial will enroll 28 participants, equally allocated to two parallel groups (n = 14 per group). Both groups will receive standard urotherapy and pelvic floor exercises as baseline interventions. The experimental group will additionally undergo 20-minute interferential stimulation twice weekly for 10 sessions under clinical supervision. Primary outcomes include maximum urine flow rate (Qmax) and severity of lower urinary tract symptoms, assessed at three times: before treatment, after treatment, and after a three-month follow-up. All statistical analyses will be conducted using SPSS software (version 26), with statistical significance set at p <0.05, Expected results It is hypothesized that using interferential stimulation will have a positive effect on clinical symptoms and urodynamic parameters in women with dysfunctional voiding. Trial registration This trial is registered in the Iranian Registry of Clinical Trials (IRCT) under the registration number IRCT20180611040061N2.